Reducing Open‐Circuit Voltage Deficit in Perovskite Solar Cells via Surface Passivation with Phenylhydroxylammonium Halide Salts. Issue 3 (2nd September 2020) - Yi, Xiaohui; Mao, Yichen; Zhang, Lu; Zhuang, Jing; Zhang, Yanyan; Chen, Ningli; Lin, Tao; Wei, Yuanzhi; Wang, Fuyi; Wang, Jizheng; Li, Cheng
Abstract: Suppressing non‐radiative recombination via passivating surface defects of perovskite films has demonstrated an excellent strategy for high‐performance perovskite solar cells (PSCs). However, it is still hard to realize both high open‐circuit voltage ( V oc ) of >1.2 V and high power conversion efficiency (PCE) of >22%,  because the optimized bandgap of perovskite films is less than 1.60 eV for efficient light harvesting and V oc deficit is generally unavoidable due to carriers recombination. Here, the surface of the perovskite film is treated with a series of phenylhydroxylammonium halide salts and it is found that all of them can remarkably prolong the carrier lifetime owing to their excellent capability of surface defects passivation. The best PSC with phenylbutylammonium bromide treatment realizes a PCE of 22.67% with a V oc of 1.216 V, corresponding to a small V oc deficit of ≈344 mV. Abstract : A series of phenylhydroxylammonium halide salts is adopted to passivate the surface of the mixed perovskite film, resulting in enormously enhanced photoluminescence (PL) intensity and prolonged carrier lifetime. As a result, the best perovskite solar cell treated with phenylbutylammonium bromide realizes a power conversion efficiency (PCE) of 22.67% with a V oc of 1.216 V, corresponding to a small V oc deficit of ≈344 mV.